Inventory Turnover and Accounts Receivable Turnover on Profitability: An Evidence of Chemical Companies Listed In IDX - Alden Rajagukguk; Harlyn Siagian (universitas teuku umar, 2021)
The profitability of a company is one of the bases for assessing the condition of a company, for that we need an analytical tool to be able to assess it. And it can be seen from the higher the inventory turnover, the better for the company to generate profits. So does account receivable turnover. The faster the cash return, the easier the company will be to continue to carry out its operational activities. The type of research used in this research is exploratorily followed by quantitative descriptive to explain the relationship and effect of inventory turnover, account receivable turnover and profitability. The result of this research are account receivable turnover has a strong and positive level of relationship to profitability. However, it has no significant effect on profitability. So does inventory turnover to profitability. Simultaneously, account receivable turnover and inventory turnover have a strong and positive level of relationship to profitability. Likewise, it has a significant effect on profitability.